SASTRA LISAN RITUAL MA’BUGI’ DALAM ACARA MANGRARA TONGKONAN DI DESA PANGLEON LEMBANG TO’PAO KABUPATEN TANA TORAJA - Dawa, Jodi; Iroth, Santje; A. Sepang, Elvie (SIWAYANG Journal: Publikasi Ilmiah Bidang Pariwisata, Kebudayaan, dan Antropologi, 2024)
The aim of this research is to describe the oral literature of the Ma'bugi' ritual in the Tongkonan mangrara event in Pangleon Lembang To'pao village, Tana Toraja district, including: 1) the form of poetry which is a symbol of joy for families celebrating thanksgiving. 2) What values are contained in Ma'bugi' as a joyous event for the Toraja people. 3) Implementation of literature learning in the Rambu' Tuka' ceremony. The research method used is descriptive method. The data sources used in this research were informants or perpetrators of the Ma'bugi' ceremony consisting of two people, one community figure, two religious figures and other written sources. The results of the research explain that in the Oral Literature Ma'bugi' Ritual at the Mangrara Tongkonan event in Pangleon Lembang To'pao Village, Tana Toraja Regency, it is a tradition for the Toraja people to be grateful for their families who have succeeded by reciting oral literature in the form of poetry during Ma' bugi'. The poems on Pa'bugiran are literature that can only be sung by certain groups of people. In the Ma'bugi' poetry there are rituals that describe the joy of a successful family, family strata, as well as happy greetings to Puang Matua/God regarding a family's achievements. Ma'bugi' oral literature is never free from symbols because: 1. Ma'bugi' poetry is a symbol of joy for people who give thanksgiving. Ma'bugi' oral literature depicts a symbol of happiness/joy for families who experienced success at that time. 2. Oral literature in Ma'bugi' is poetry that is always closely related to rituals as symbols in the Rambu Tuka' ceremony and is an important part of the ceremony. 3. Ma'bugi' poems are a special symbol in the Rambu Tuka' ceremony, especially in identifying the caste of the family.